Intraoral findings in newborns: prevalence and associated factors - Cláudia Lobelli Chandler; Isabelita Duarte Azevedo; Manoelito Ferreira Silva Junior; Johnnatas Mikael Lopes; Manuel Antonio Gordón-Núñez; Silvana Alves Pereira (Universidade Estadual de Campinas, 2018)
Aim: To investigate the prevalence of intraoral characteristics and associated factors with neonatal and parent variables in a group of Brazilian newborns. Methods: This cross-sectional study with a descriptive and inferential approach, whose data was obtained through clinical examination, interview and the collection of medical record information. The sample was selected from babies up to three days old, of both sexes, and born between January and December 2013 in the Ana Bezerra University Hospital, in the city of Santa Cruz-RN, Brazil. The exposure variables included neonatal (sex, weight, gestational age, type of delivery and Apgar score) and parent (presence of systemic disease(s), drug use and consanguinity between the parents) variables. Descriptive analysis and Poisson regression were performed to estimate the ratio of gross and adjusted prevalence of intraoral findings (Epstein pearls, Bohn's nodule, dental lamina cyst and ankyloglossia) with the neonatal and parent variables (p<0.05). Results: Of a total of 168 examined newborns, 56.5% (n=95) were male. The most prevalent intraoral feature was the fibrous cord of Magitot, 62.5% (n=105), and the most frequent alteration was Epstein pearls, 44.6% (n=75). Female gender was a factor for Bohn's nodule (OR=0.90; 95%CI:0.82-0.99), and no tobacco use by the father was a protective factor for Epstein pearls (OR=0.73;95%CI:0.55-0.97). Additionally, lower mother's age, between 20-34 years  of age (OR=1.58;95%CI:1.07-2.35) and under 19 years of age (OR=1.61; 95%CI:1.03-2.52) increases the chance of having Epstein pearls. Conclusion: There was a high prevalence of alterations in the newborns' oral cavities and there were associations between neonatal and parent variables.